1998
DOI: 10.1016/s0009-9236(98)90161-8
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CYP2E1 activity in liver transplant patients as measured by chlorzoxazone 6-hydroxylation*

Abstract: Objective-To examine the phenotypic expression of CYP2E1 in liver transplant patients, as measured by the in vivo probe chlorzoxazone, and to evaluate CYP2E1 activity over time after transplantation.Methods-Thirty-three stable liver transplant patients were given 250 mg chlorzoxazone within 1 year after transplantation as part of a multiprobe CYP cocktail; urine and blood were collected for 8 hours. Chlorzoxazone and 6-hydroxychlorzoxazone concentrations were determined by HPLC. Twenty-eight healthy control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Chlorzoxazone 6-hydroxylation has been commonly used to measure human CYP2E1 activity (Lucas et al, 1996(Lucas et al, , 1999Haufroid et al, 2002). Measurement of chlorzoxazone and trimethadione metabolism by CYP2E1 has also been used as an indicator for liver diseases in vivo and in vitro (Dilger et al, 1997;Burckart et al, 1998;Mishin et al, 1998;Dupont et al, 2000). An alternative method for measuring CYP2E1 activity has been to analyze p-nitrophenol hydroxylation ( p-nitrocatechol formation) (Zerilli et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Chlorzoxazone 6-hydroxylation has been commonly used to measure human CYP2E1 activity (Lucas et al, 1996(Lucas et al, , 1999Haufroid et al, 2002). Measurement of chlorzoxazone and trimethadione metabolism by CYP2E1 has also been used as an indicator for liver diseases in vivo and in vitro (Dilger et al, 1997;Burckart et al, 1998;Mishin et al, 1998;Dupont et al, 2000). An alternative method for measuring CYP2E1 activity has been to analyze p-nitrophenol hydroxylation ( p-nitrocatechol formation) (Zerilli et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…CHZ, a centrally acting muscle relaxant, is primarily hydroxylated by CYP2E1 to 6-hydroxy CHZ and therefore has been extensively used as a selective probe for measuring hepatic CYP2E1 activity in humans. [17][18][19][20][21] Subjects were asked to avoid certain foods (grapefruit, vegetables from the mustard green family, and beverages containing xanthine and alcohol) for at least 72 hours, and, when possible, nonessential medications were discontinued one week before this test to reduce the chances of drug interference. Blood and urine samples were collected for 8 hours after administering a 500-mg dose of chlorzoxazone orally, followed immediately by 240 mL of water.…”
Section: Methodsmentioning
confidence: 99%
“…Over the decade, measurement of the metabolic rate of chlorzoxazone and trimethadione by CYP2E1 was used as an indicator for liver diseases in vivo and in vitro. [2][3][4][5] As CYP2E1 is an ethanol inducible enzyme, its functional characterization has been focused on alcoholic liver diseases; 6 therefore our knowledge of CYP2E1 in carcinogenesis is limited. Until recently, an in vitro study has revealed that overexpression of CYP2E1 induces cytotoxicity in human hepatoblastoma cell line (HepG2), 7 which suggested that expression of CYP2E1 may play a role in tumor cell proliferation.…”
mentioning
confidence: 99%